Implementation of Word Square Oriented Lesson Study in Educational Sociology Learning Outcomes - Jauhan Budiwan; Meidawati Suswandari (STAI Hubbulwathan Duri, 2023)
The purpose of this study was to describe the implementation of lesson study using word squares in educational sociology courses. Using lesson research with qualitative approach, this study involved one class of 29 pre-service elementary school teachers in semester VIA on the Educational Sociology course. Two lecturers were involved as observers. The instruments included observation sheet for open class activities and lesson learned reports. The data were analyzed using interactive technique. It is concluded that the lesson study was implemented to students using Word Square in three stages (Plan, Do, and See). Plan stage includes preparing a table of lesson study activity plans, day and date, materials, activities (pre-activity, main activity, and post-activity), lecture instruments (Lecture Unit/SAP), learning media, handouts, model lecturer, observation sheet, and assessment/evaluation sheet. Do stage includes implementing educational sociology learning with the theme “Education and Social Mobilization Stratification” as planned (Plan stage). See stage is a reflection activity from the previous stage by the observers